Pyrite δ34S and Δ33S constraints on sulfur cycling at sublacustrine hydrothermal vents in Yellowstone Lake, Wyoming, USA. (15th November 2019) - Fowler, Andrew P.G.; Liu, Qiu-li; Huang, Yongshu; Tan, Chunyang; Volk, Michael W.R.; Shanks, W.C. Pat; Seyfried, William
Abstract: Sulfur isotope values (δ 34 S and Δ 33 S) of pyrite in sediment from steam-heated hydrothermal vents on the floor of Yellowstone Lake (WY) were measured using secondary ionization mass spectrometry (SIMS). The high resolution of the SIMS data place important constraints on sulfur cycling processes at/near the vent fluid-lake water interface. Pyrite with a distinct mantle-basalt (δ 34 S = 0‰) isotope composition (δ 34 S = +0.5 to +3.1‰) replaces pyrrhotite during incipient stages of alteration at moderately high temperature. Disseminated cubic pyrite (δ 34 S = +2.0 to +5.3‰) occurs in zones where more extensive oxidation is likely. Framboidal pyrite with δ 34 S values ranging from –5.2 to +4.1‰ and Δ 33 S up to +0.30‰ suggest formation from low-temperature microbial sulfate reduction in sediments near but not directly in the vent fluid up-flow zone. The co-occurrence of pyrite with S isotope values characteristic of distinct formation processes, coupled with notable intra-crystal S isotope variations, suggests the venting locus is dynamic in time and space.